#TITLE_ALTERNATIVE# - HANDAYANI, NURITA
Buildings should be designed to give the best performance under earthquake loading. Some devices have been attached to reduce the structural response under earthquake loading. The devices used to reduce dynamic response of building are tuned mass damper (TMD) and multiple tuned mass dampers (MTMD). MTMD consist of some TMD with unequal natural frequency that is distributed over a certain frequency range. Some studies shown that MTMD's optimum combination parameters (mass ratio, damping ratio, and frequency) can improve structural performance better than TMD, especially for random loading. This study conducts to understanding about the behavior of structural system with MTMD experimentally, and verify with numerical approaches. A 3-DOF scaled model used in the experimental study. The 1:10 scaled model represents regular structures with dominant first mode. TMD and MTMD were attached to the main structures with the total mass ratio of TMD/MTMD is about ten percent of the story mass. Three different numbers of TMD were used, i.e. 1TMD, 3TMD, and 5TMD. The locations and distributions of MTMD were also varied from. The models without any TMD were used as a benchmark model to evaluate the effectiveness of MTMD. Identification procedures were carried out to each structural model and dampers to determine the dynamic properties. The experimental study was conducted using shake table with variated harmonic motions. The responses were recorded using accelerometers and LVDT. The results show that MTMD can reduce the structural displacement under harmonic motions, thus confirming numerical results. Having MTMD instead of TMD also increased the robustness of the systems, shown by the reduction of structural responses for various input motions. Using all MTMD located on the top story produced best results compared to other placements or distributions.